Barium isotopic composition of the mantle: Constraints from carbonatites. (1st June 2020) - Li, Wang-Ye; Yu, Hui-Min; Xu, Juan; Halama, Ralf; Bell, Keith; Nan, Xiao-Yun; Huang, Fang
Abstract: To investigate the behaviour of Ba isotopes during carbonatite petrogenesis and to explore the possibility of using carbonatites to constrain the Ba isotopic composition of the mantle, we report high-precision Ba isotopic analyses of: (1) carbonatites and associated silicate rocks from the only active carbonatite volcano, Oldoinyo Lengai, Tanzania, and (2) Archean to Cenozoic carbonatites from Canada, East Africa, Germany and Greenland. Carbonatites and associated phonolites and nephelinites from Oldoinyo Lengai have similar δ 137/134 Ba values that range from +0.01 to +0.03‰, indicating that Ba isotope fractionation during carbonatite petrogenesis is negligible. The limited variation in δ 137/134 Ba values from −0.03 to +0.09‰ for most carbonatite samples suggests that their mantle sources have a relatively homogeneous Ba isotopic composition. Based on the carbonatites investigated in this work, the average δ 137/134 Ba value of their mantle sources is estimated to be +0.04 ± 0.06‰ (2SD, n = 16), which is similar to the average value of +0.05 ± 0.06‰ for mid-ocean ridge basalts. The lower δ 137/134 Ba value of −0.08‰ in a Canadian sample and higher δ 137/134 Ba values of +0.14‰ and + 0.23‰ in two Greenland samples suggest local mantle isotopic heterogeneity that may reflect the incorporation of recycled crustal materials in their sources.